Middle Miocene (Serravallian) rhodoliths and coralline algal debris in carbonate ramps (Betic Cordillera, S Spain) - Aguirre, Julio; Braga, Juan C. (Frontiers in Earth Science, 2022)
Serravallian (middle Miocene) coralline algal assemblages at the southern margin of the Guadalquivir Basin (southern Spain) occur as rhodoliths preserved in situ or very closely to their growth habitats (autochthonous-parautochthonous assemblages), and as reworked remains (allochthonous assemblages). The former assemblages consist of spherical rhodoliths built up by encrusting to warty plants, as well as of large fragments of branches, while the latter mostly are unrecognizable small fragments that occur in channeled packstone-grainstone beds. In both cases, the most abundant components are members of the order Hapalidiales (Mesophyllum roveretoi, Mesophyllum sp. Lithothamnion ramosissimum, and less frequently Phymatolithon group calcareum and Lithothamnion valens). Laminar growths of Lithoporella minus as well as branches of Spongites group fruticulosus and Sporolithon sp. occur very rarely. There are also anecdotal records of Subterraniphyllum thomasii, extending its upper stratigraphic range up to the Serravallian in the western Tethys. The autochthonous-parautochthonous coralline algal assemblages formed in a middle ramp, at several tens of meters of water depth, as suggested by the dominance of Hapalidiales. The allochthonous assemblages represent fragments of coralline algae derived from the middle ramp and redeposited in deeper settings, most likely outer ramp, due to storm currents.